Assessment of the Level of Pesticide Contamination in Amphibians from Cocoa Plantations at Ojo Camp-Ugboke, Southern Nigeria - O. Edo-Taiwo; M. S. O. Aisien (Journal of Applied Sciences and Environmental Management, 2023)
Amphibian skin is extremely permeable to environmental contaminants and their health is inextricably linked to environmental health. Hence the objective of this study was to evaluate the level of pesticide contamination in amphibian tissues and their environment (soil and sediment) at Ojo Camp-Ugboke cocoa plantations in Edo State, southern Nigeria using HP 5890 series gas chromatography system coupled with an Electron Capture Detector (ECD). Data obtained showed that thirteen organochlorine pesticides, one triazine herbicide, carbamate, and organophosphate were found in high concentrations. All pesticides components were detected in amphibian tissues, most with higher concentrations than other samples. The high permeability of amphibian skin is responsible for the detected in-tissue concentrations. Pesticide residues in amphibian tissues are not only harmful to their health, but also pose a health risk to those who consume amphibian meat as a delicacy. Local farmers' unabated/unregulated use of pesticides may contribute in amphibian population decline. For a healthier environment, it is best to increase public awareness while also supporting routine monitoring and regulation by relevant agencies.